The Role of Religious Education in Forming Public Civilized Humans - Syarif Hidayatullah; Harmuji; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract - This article discusses juvenile delinquency, corruption, sexual harassment in public, which causes violent land grabbing which causes lives to be lost, reckless drivers, this is a loss of public decency. Problems that can occur due to economic factors, religious education is not used or carried out in daily behavior, which raises the question of what is the role of religious education in shaping public civilized people? Humans are the most perfect creatures, there is a lot of potential inherent in humans, as the leader of this earth, the caliph, then humans have a relationship with humans, social and God.